ECONOMIC EFFECTIVENESS CONCEPT IN THE CONTEXT OF SCIENTIFIC SCHOOLS EVOLUTION (INNOVATIVE ECONOMY, 2020)
Lymar V.V. ECONOMIC EFFECTIVENESS CONCEPT IN THE CONTEXT OF SCIENTIFIC SCHOOLS EVOLUTIONPurpose. The purpose of an investigation is analysis and comparison of views of representatives of different scientific schools and modern scientists on the economic effectiveness concept.Methodology of research. During the investigation there were used such scientific methods: analysis (investigation of scientific schools theories); comparison (studying views of classicists of economic theory); concretization (definition of concrete features of approaches to understanding economic effectiveness concept from the point of view of modern scientists) and analogy (comparison of classicists’ views and modern scientists on the economic effectiveness definition).Findings. It is revealed that the effectiveness definition evolution has the long history. It is established that for the first time this effectiveness definition in economic theory appeared in works of the classical theory representative V. Pareto. It is determined that the model of economic efficiency suggested by V. Pareto means that society’s welfare reaches maximum and resources distribution becomes optimal if any change of this distribution does not make worse condition even one of the subjects of economic system.A comparative analysis is carried out, which established that the classical economic theory and its representatives A. Smith and D. Ricardo do not study effectiveness concept concerning economics. A. Smith defined economic laws as objective reality, D. Ricardo defined dependence of products costs from labor (labor cost theory) and defined the main task for the classical political economy: to define laws which manage profits distribution.K. Menger, one of the marginalism founders, in the 1970th worked out and gave prove the concept of public good and subjective value where he presented a product not as a thing with physical features but as a bearer of features that are useful for a consumer.It is justified that economic effectiveness is a result of an economic system which shows the ratio of useful final results of its operation to spent resources. On the micro-level it is the ratio of produced goods (volume of selling) to costs (labor, capital). On the macro-level the economic effectiveness is defined as the ratio of GDP to costs (labor, capital, land).Originality of the article is the definition of approaches to studying the aspects of economic effectiveness concept.Practical value. Results got during the investigation, enrich available base of modern economic theory.Key words: economic effectiveness; limited resources; innovation and technological growth; activity results; economics competitiveness.
Keywords: Key words; economic effectiveness; limited resources; innovation and technological growth; activity results; economics competitiveness.